Development of a methodology for the formation and adjustment of the catalog of defense forces capabilities - Oleh Surkov (Eastern-European Journal of Enterprise Technologies, 2021)
The study results have made it possible to devise a methodology for the formation and adjustment of the Defense Forces Capabilities Catalog using cluster analysis and the developed tree-like system of basic indicators characterizing groups and subgroups (clusters). That enables stakeholders to form and adjust the Defense Force Capabilities Catalog with the proper quality, according to the uniform developed algorithm and defined identifiers (features).